2009
DOI: 10.1038/jid.2009.112
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Stroke in Patients with Psoriasis

Abstract: Psoriasis is a chronic Th-1 and Th-17 inflammatory disease. Chronic inflammation has also been associated with atherosclerosis and thrombosis. The purpose of this study was to determine the risk of stroke in patients with psoriasis. We conducted a population-based cohort study of patients seen by general practitioners participating in the General Practice Research Database in the United Kingdom 1987-2002. Mild psoriasis was defined as any patient with a diagnostic code of psoriasis but no history of systemic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
359
1
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 386 publications
(395 citation statements)
references
References 37 publications
15
359
1
11
Order By: Relevance
“…79 Recent high quality work revealed an increased risk of stroke for mild and severe psoriasis. 80 In particular, severe psoriasis confers an increased risk of stroke not explained by major risk factors alone. 80 This increased risk of PVD and CVD was confirmed by another study, but analysis did not control for other risk factors.…”
Section: Peripheral Vascular Disease and Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…79 Recent high quality work revealed an increased risk of stroke for mild and severe psoriasis. 80 In particular, severe psoriasis confers an increased risk of stroke not explained by major risk factors alone. 80 This increased risk of PVD and CVD was confirmed by another study, but analysis did not control for other risk factors.…”
Section: Peripheral Vascular Disease and Cerebrovascular Diseasementioning
confidence: 99%
“…80 In particular, severe psoriasis confers an increased risk of stroke not explained by major risk factors alone. 80 This increased risk of PVD and CVD was confirmed by another study, but analysis did not control for other risk factors. 25 While these studies suggest an increased risk for vascular disease, further prospective trials should aim to delineate the possibility of a causal relationship.…”
Section: Peripheral Vascular Disease and Cerebrovascular Diseasementioning
confidence: 99%
“…Psoriasis hastalarında diabetes mellitus, atrial fibrilasyon, hipertansiyon, aterosklerozis, stroke, miyokard enfarktüsü, kardiyovasküler mortalite ve metabolik sendrom oranlarının yüksek olduğu uzun zamandır bilinen bir gerçektir [2][3][4][5][6][7] . Son yıllarda nötrofil ve trombosit sayısının lenfosit sayısına (N/L ve T/L oranı) oranının sistemik inflamasyonun bir göstergesi olabileceği ve birçok kardiyovasküler hastalık, maliniteler ve kronik inflamatuvar hastalıklarda prognoz ile ilişkili olduğu gösterilmiştir.…”
Section: Introductionunclassified
“…16 Large clinical trials revealed an increased risk of myocardial infarction and stroke in patients with psoriasis. 17,18 We predict that these high-impact topics will continue to be frequently published in contemporary literature.…”
Section: Discussionmentioning
confidence: 99%